2003
DOI: 10.4319/lo.2003.48.2.0618
|View full text |Cite
|
Sign up to set email alerts
|

In situ determination of the quantum yield of phytoplankton chlorophyll a fluorescence: A simple algorithm, observations, and a model

Abstract: Vertical profiles of the in situ quantum yield of fluorescence of chlorophyll a, f , were derived with an algorithm from spectral underwater radiometer measurements. Select inherent optical properties were obtained from an initial radiance reflectance inversion that was optimized by comparing retrieved estimates of phytoplankton absorption with independent measurements. The comparison of chlorophyll concentrations produced by the algorithm to measured values allowed validation of the inversion. Fluorescence qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
113
2

Year Published

2005
2005
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(125 citation statements)
references
References 61 publications
10
113
2
Order By: Relevance
“…Babin et al (1996) show frequency distributions for a* and Q a * observed in the open ocean waters of different basins, both vary over nearly an order of magnitude. As for j f , it varies in a more complicated manner (Morrison 2003;Schallenberg et al 2008). As a consequence, the fluorescence-Chl a relationship for a given fluorometer varies according to environmental conditions.…”
Section: _1mentioning
confidence: 99%
See 1 more Smart Citation
“…Babin et al (1996) show frequency distributions for a* and Q a * observed in the open ocean waters of different basins, both vary over nearly an order of magnitude. As for j f , it varies in a more complicated manner (Morrison 2003;Schallenberg et al 2008). As a consequence, the fluorescence-Chl a relationship for a given fluorometer varies according to environmental conditions.…”
Section: _1mentioning
confidence: 99%
“…However, the proportionality of [Chl a] and F is known to be modulated by the taxonomic composition and physiological acclimation mechanisms (essentially related to light and/or nutrient history), which both determine the variability in a*, j f , as well as Q a * (e.g., Falkowski and Kolber 1995;Babin et al 1996;Morrison 2003;Schallenberg et al 2008). Babin et al (1996) show frequency distributions for a* and Q a * observed in the open ocean waters of different basins, both vary over nearly an order of magnitude.…”
Section: _1mentioning
confidence: 99%
“…9, bottom) yields measured in situ in surface waters of the world (Ostrowska et al 1997;Maritorena et al 2000;Morrison 2003). A comparison of ϕ est and CFE is shown in the upper left panel of Fig.…”
Section: Comparing the Finite-depth Modis Algorithm To A Complete Depmentioning
confidence: 99%
“…As such, field validation of fluorescence algorithms will require great care. The time of sampling and the incident irradiance will have to match those encountered by the MODIS sensor, otherwise, the time and irradiance dependence of ϕ will affect the results (e.g., Morrison 2003).…”
Section: Comments and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation